Definition et visualisation du type du contexte socio-ecologique (CSET). - Fradi, Fajr; Diwediga, Badabate; Le, Quang Bao; Bonaiuti, Enrico; Lala-Pritchard, Tana; Hemingway, Charlotte (2017)
Under the Economics of Land degradation initiative (ELD), scientists from ICARDA are collaborating with developments to develop the GeOC tool. It is a new web-based GIS tool to define context specific options for sustainable land management required to achieve Land Degradation Neutrality (LDN). This video illustrates the process of defining and visualizing the socio-ecological context type in the GeOC tool. To check the GeOC tool, please follow this link: http://geoc.mel.cgiar.org To learn more about the project under which the GeOC tool is developed, please follow this link: https://mel.cgiar.org/projects/geoxc Acknowledgments: 'GeOC is the result of the synergic efforts by CGIAR Research Program on Dryland Systems (CRP-DS), the International Center for Agricultural Research in the Dry Areas (ICARDA) and its Geoinformatics Unit (GU), and is powered by iMMAP, Codeobia, D-Space and Amazon Web Services.'